(untitled) (Faridpur Medical College Journal, 2020)
Coronary artery atherosclerosis (CAA) leads to ischemic heart disease and that is the most common cause of cardiac deaths worldwide. The incidence is more among the elderly people, but now gradually increasing among the young. The study was done to evaluate the prevalence of CAA in different age group by post-mortem study. An observational study was conducted in the department of Pathology of Faridpur Medical College (FMC). In this study total 53 postmortem histopathological examination of heart were done and analyzed, of them 37 were male and 16 were female. Among all, CAA was found in 8 cases and all were male. Regarding age, 4(50%) cases were in the age group from 41 to 50 years, 3 cases were in age of above 60 years and one case was in the age group from 51 to 60 years. Left CAA was observed in 6(75%) cases, both right and left CAA was found in remaining 2(25%) cases but none was found to involve only right coronary artery. Lowest age of involvement of CAA was 42 years that involved left coronary artery. This study shows that the prevalence of CAA is increasing among the younger age group. Faridpur Med. Coll. J. Jan 2020;15(1): 21-23